2019
DOI: 10.1080/00480169.2019.1667282
|View full text |Cite
|
Sign up to set email alerts
|

A serological survey of canine respiratory coronavirus in New Zealand

Abstract: Aims:To determine the seroprevalence of canine respiratory coronavirus (CRCoV) in New Zealand dogs, and to explore associations with age, sex, breed, month, and geographical region of sampling and reported presence of clinical signs suggestive of respiratory disease. Methods: A total of 1,015 canine serum samples were randomly selected from submissions to a diagnostic laboratory between March and December 2014, and were analysed for CRCoV antibodies using a competitive ELISA. Logistic regression analysis was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Most CRCoV serological testing methods utilise a high degree of similarity between CRCoV and bovine coronavirus (BCoV) spike proteins and resulting serological crossreactivity [ 11 ]. This study used a commercial ELISA kit (BIO K 392 Monoscreen AbELISA Bovine coronavirus/Competition, Bio-X diagnostics, Rochefort Belgium) as previously described [ 12 ]. It is a competitive ELISA with wells coated with BCoV antigens.…”
Section: Methodsmentioning
confidence: 99%
“…Most CRCoV serological testing methods utilise a high degree of similarity between CRCoV and bovine coronavirus (BCoV) spike proteins and resulting serological crossreactivity [ 11 ]. This study used a commercial ELISA kit (BIO K 392 Monoscreen AbELISA Bovine coronavirus/Competition, Bio-X diagnostics, Rochefort Belgium) as previously described [ 12 ]. It is a competitive ELISA with wells coated with BCoV antigens.…”
Section: Methodsmentioning
confidence: 99%
“…Several epidemiological and serological studies have demonstrated that CRCoV is one of the etiological agents involved in canine infectious respiratory disease (CIRD) in dog shelters and kennels worldwide ( Maboni et al, 2019 ; Mitchell et al, 2017 ; More et al, 2020 ). Experimental studies of CRCoV infection in dogs from geographically distinct regions have shown signs of mild respiratory disease, including nasal discharge, sneezing and coughing ( Mitchell et al, 2013 ).…”
Section: Relevant Coronaviruses In Veterinary Medicinementioning
confidence: 99%
“…It results in being categorized as a wicked problem [16] due to its complexity and such uncertain behavior. Due to this problem, the researchers can still not get the vaccine or medicine for its complete cure [17,18,19,20,21,22].…”
Section: Figure 1 Worldwide Actual Covid-19 Status As On 30 June 2020mentioning
confidence: 99%